Facial emotion perception impairments in schizophrenia patients with comorbid antisocial personality disorder. (28th February 2016) - Tang, Dorothy Y.Y.; Liu, Amy C.Y.; Lui, Simon S.Y.; Lam, Bess Y.H.; Siu, Bonnie W.M.; Lee, Tatia M.C.; Cheung, Eric F.C.
Abstract: Impairment in facial emotion perception is believed to be associated with aggression. Schizophrenia patients with antisocial features are more impaired in facial emotion perception than their counterparts without these features. However, previous studies did not define the comorbidity of antisocial personality disorder (ASPD) using stringent criteria. We recruited 30 participants with dual diagnoses of ASPD and schizophrenia, 30 participants with schizophrenia and 30 controls. We employed the Facial Emotional Recognition paradigm to measure facial emotion perception, and administered a battery of neurocognitive tests. The Life History of Aggression scale was used. ANOVAs and ANCOVAs were conducted to examine group differences in facial emotion perception, and control for the effect of other neurocognitive dysfunctions on facial emotion perception. Correlational analyses were conducted to examine the association between facial emotion perception and aggression. Patients with dual diagnoses performed worst in facial emotion perception among the three groups. The group differences in facial emotion perception remained significant, even after other neurocognitive impairments were controlled for. Severity of aggression was correlated with impairment in perceiving negative-valenced facial emotions in patients with dual diagnoses. Our findings support the presence of facial emotion perception impairment and its association with aggression in schizophrenia patients with comorbid ASPD. Highlights: SCZ patients with ASPD had more impaired facial emotion perception than SCZ patients. Facial emotion misperception was not attributable to other cognitive impairments. Aggression was correlated with misperception of negative-valenced facial emotions.